2001
DOI: 10.1063/1.1414298
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature crystalline Ag–Ni alloy formation from silver and nickel nanoparticles entrapped in a fatty acid composite film

Abstract: Nanoparticles of silver and nickel were grown in thermally evaporated fatty acid (stearic acid) films by immersion of the film sequentially in solutions containing Ag+ ions and Ni2+ ions. Attractive electrostatic interaction between the metal cations and the carboxylate ions in the fatty acid film leads to entrapment of the cations in the film. Thereafter, the metal ions were reduced in situ to yield nanoparticles of Ag and Ni of ∼30 nm diameter within the fatty acid matrix. Thermal treatment of the stearic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Moreover, one has to get in mind that Ni and Ag do not form stable alloys [21,22]. Therefore, we may infer that some metastable supported NiAg alloy, of high metal surface area, arose in the hydrazine media but were not detected by the tools we used to characterize the catalysts.…”
Section: H 2 Adsorptionmentioning
confidence: 96%
See 4 more Smart Citations
“…Moreover, one has to get in mind that Ni and Ag do not form stable alloys [21,22]. Therefore, we may infer that some metastable supported NiAg alloy, of high metal surface area, arose in the hydrazine media but were not detected by the tools we used to characterize the catalysts.…”
Section: H 2 Adsorptionmentioning
confidence: 96%
“…Indeed, only metastable NiAg alloys have been observed in specific conditions [21,22]. These alloys give rise to phase separation and reformation of Ni and Ag particles with time on stream [21]. Our study aimed to re-investigate this system in preparation conditions not reported before, namely the hydrazine media and using silica as a support.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations